Scapulothoracic and Glenohumeral Kinematics During Daily Tasks in Users of Manual Wheelchairs - Zhao, Kristin D.; Van Straaten, Meegan G.; Cloud, Beth A.; Morrow, Melissa M.; An, Kai-Nan; Ludewig, Paula M. (Frontiers in Bioengineering and Biotechnology, 2015)
Background Rates of shoulder pain in individuals who use manual wheelchairs as their primary means of mobility have been reported to be as high as 70% during activities of daily living. Current prevailing thought is that mechanical impingement of the soft tissues that reside within the subacromial space between the humeral head and coracoacromial arch is a major contributor to the shoulder pain in users of manual wheelchairs. The subacromial space size is directly related to the kinematics at the shoulder joint. Yet to be answered are questions about which common daily tasks are characterized by the most potentially detrimental kinematics. Objective The purpose of this analysis was to quantify and compare potentially detrimental kinematics in three common tasks performed by individuals with SCI and shoulder pain. These data will add to the body of knowledge, and test common assumptions about relative risk of tasks. Design A cross-sectional study of 15 manual wheelchair users with shoulder pain. Methods Electromagnetic surface sensor measures of mean and peak scapulothoracic internal and downward rotation, anterior tilt, and glenohumeral internal rotation were compared across propulsion, weight relief, and scapular plane abduction tasks using one-way repeated measures ANOVA. Results Statistical differences were observed between the tasks for all rotations. Mean scapulothoracic anterior tilt was greater in weight relief and propulsion than during scapular plane abduction (24, 23, and 13 degrees of anterior tilt, respectively). Mean GH axial rotation during weight relief was more internally rotated than during propulsion and scapular plane abduction (9, 26, and 51 degrees of external rotation, respectively). Limitations Surface-based measures of kinematics are subject to skin motion artifact, especially in translation which was not addressed in this study. Conclusions Each task presented with specific variables that might contribute to risk of developing shoulder “impingement” and pain. These data may assist therapists in their assessment of movement contributions to shoulder pain in this population, as well as in subsequent treatment planning.